The impact of sleep on the Th17/Treg axis and cytokine levels in patients with major depressive disorder - Tiantian Fu; Wanting Zhang; Shengxiao Zhang; Feng Tian (Neuroscience Research)
A cross-sectional study was designed to investigate the relationship between immune parameters and sleep quality in patients with depression, in which 65 depression patients and 63 healthy controls were enrolled between August 2021 and June 2024, with sleep assessments ultimately completed by 59 depression patients following exclusions. Th17/Treg cell ratios and cytokine levels were measured using flow cytometry and cytometric bead array (CBA), and correlation and regression analyses were performed to evaluate associations between sleep quality and inflammatory markers. Elevated Th17 cells, Th17/Treg imbalance, and increased IL-6 and IL-17 levels were observed in depression patients compared to controls (all P < 0.0167), while higher IL-4, IL-6, and IL-17 levels were found in patients with sleep disorders (all P < 0.0071). Th17/Treg ratios were positively correlated with sleep disturbance scores, whereas Treg levels showed an inverse correlation, and IL-6, IL-17, IFN-γ, and TNF-α levels were positively associated with sleep disturbances (all P < 0.05). Furthermore, IL-6 and IFN-γ were identified as significant predictors of poor sleep quality (all P < 0.05). These findings suggest that inflammatory dysregulation, particularly elevated IL-6 and IFN-γ, is associated with poorer sleep quality in depression patients, providing potential insights for enhanced clinical management.